Sosialisasi Dan Pelatihan Diversifikasi Produk Roti Manis Dengan Bahan Lokal Untuk Meningkatkan Gizi Masyarakat Di SMK Muhammadiyah Kabil Batam - Miratia Afriani; Eva Amalia; Tito Pratama; Hans Steven Sembiring (CV. Multi Kreasi Media, 2025)
Efforts to improve community nutrition can be carried out through education and the development of nutritious food products based on local ingredients. This activity aimed to provide socialization and hands-on training to students of SMK Muhammadiyah Kabil Batam on how to diversify sweet bread products by incorporating local food ingredients such as sweet potatoes, pumpkins, and bananas. The methods included nutrition and food security education, product demonstrations, and student practice sessions. The results showed high student enthusiasm and successful creation of sweet bread variations that were both visually appealing and more nutritious. This activity also increased students’ awareness of the importance of consuming local food and opened opportunities for health-oriented culinary entrepreneurship. Therefore, the training contributed to improving culinary skills, nutrition knowledge, and sustainable use of local resources.